Weight gain, behavioral and cortisol changes after orchiectomy with or without local anaesthesia in piglets - Barticciotto, Leticia Sturlini; Luna, Stelio Pacca Loureiro [UNESP]; De Sï¿½ Lorena, Sï¿½lvia Elaine Rodolfo; Telles, Filipe Garcia [UNESP]; Berto, Dirlei Antï¿½nio [UNESP] (Universidade Estadual de Londrina, 2016)
The aim of this study was to investigate the effect of intratesticular local anesthesia on weight gain and behavioral and cortisol changes in piglets submitted to castration. Study design was a randomized controlled trial. Twenty-nine male Landrace crossbred piglets aged 3 to 6 days were used. The piglets were randomly divided into two groups: orchiectomy with anesthesia (A, n = 15) and orchiectomy without anesthesia (NOA, n = 14). Piglets in the A and NOA groups were treated with 0.5 mL of intratesticular 2% lidocaine with a vasoconstrictor in each testicle and 0.5 mL of intratesticular 0.9% sodium chloride, respectively. Blood samples were collected from all animals immediately after surgery and at 3 and 6 days postoperatively for measurement of the serum cortisol concentration. Behavior was assessed daily for 6 days by two observers blinded to the treatment. Weight was measured at the same time as cortisol measurement. Analysis of variance followed by the Student-Newman-Keuls test was used to investigate differences in time within and between the two groups. Mean times of six evaluations done for 90 minutes during 6 days of each behavior were compared by Tukey t test. The level of statistical significance was 5%. The serum cortisol concentration was higher immediately after surgery than at 3 and 6 days postoperatively in both groups. Weight gain was greater at 3 and 6 days postoperatively in the A group than in the NOA group. Intratesticular local anesthesia before castration in piglets is technically practical, is in accordance with good welfare practice, and improves short-term weight gain in piglets submitted to castration.
Keywords: Behavior; Castration; Lidocaine; Pig